Treatment of Emulsified Oil in Produced Water from Oil wells by Adsorption on to Corn-Cob as Sorbent - Khalid, Mohamed Ghazi (Nahrain University College of Engineering Journal, 2014)
In this work , a fixed –bed systemhas been used to study the performanceof corn-cob as low cost adsorbent forTreatment of dispersed oil droplets inoil-well product water in this system .In effect of initial oil content (600-1500ppm), volumetric flow rate (2-5L/min),Bed height (25-35cm) and particle size(1.05-1.6mm) were studied. The resultsshow that removal oil efficiencyreaches high percent with decreasing ofinitial oil concentration, volumetricflow rate particle size and increasing ofbed height.